O CME no sistema municipal de ensino: um estudo sobre a atuação do conselho municipal de educação de Cachoeiro de Itapemirim-ES - Portinho, Diego Buffolo (2019)
This study integrates the research line School Practice, Teaching, Society and Teacher Training of the Graduate Program in Teaching, Basic Education and Teacher Training of the Federal University of Espírito Santo and aims to discuss the performance of the Municipal Council of Education of Cachoeiro de Itapemirim-ES (CME / CI) as an advisory body and deliberative educational policy within the Municipal Education System (SME). In this sense, it’s based on references of some theorists of the field of educational policy (ARAÚJO, 2012, 2016, 2017, 2018; CURY, 1978, 2002, 2006, 2008, 2010; GOHN, 1992, 2011, 2019; SAVIANI, 1999 , 2017) and of the counselor practice (BORDALO, 2016; BORDIGNON, 2009; BATISTA 2009, 2010, 2018; MARCELINO, 2013) in dialogue with some Freirean concepts (FREIRE 1995, 1996, 1999, 2000, 2001, 2016). From a methodological perspective, it’s a qualitative research that develops through a case study. The research subjects are the counselors of the CME / CI. Regarding the procedures employed in the composition of the study, we highlight the use of bibliographic consultation, documentary consultation and semi-structured interview. During the semi-structured interview, the data were collected through an audio recorder, with subsequent transcription of the dialogues and with the help of a field diary produced by the researcher. The organization, analysis and discussion of the data were based on the triangulation technique assumed by Triviños (1987). In this context, we chose to construct three categories named: autonomy, dialogicity and politics that emerged during the research, in the interface of theoretical references in interaction with empirical data. The study's considerations point to the need to institutionally strengthen the CME / CI through dialogue channels that facilitate communication and integrated work between the Council, the Education Secretariat, and other institutions that make up the SME structure, giving it more autonomy and capacity for political action, in order to comply with the legal frameworks that establish the purposes and attributions for which the CME / CI was established. In the field of consultative action and political deliberation, countless actions were registered in order to de-legitimize the protagonism of the council, evidenced by the reduction of its autonomy, capacity for dialogue and political action, even in the face of all the mobilization and commitment of the councilors, act to promote a democratizing space. We understand that the council has done little to advise and deliberate on educational policy, whereas most of the normative acts practiced demonstrate that the CME / CI acts to regulate and legitimize decision-making practices that have already been established by the municipal government, within other instances of the SME without their participation. In this sense, the object of educational policy, understood as the guarantee of the right to education, is being reduced to the discretionary interests of the public power and its meaning as a state policy is being emptied